Twenty five years of medical informatics education at Heidelberg/Heilbronn: discussion of a specialized curriculum for medical informatics - Leven, Franz-Josef; Haux, Reinhold (International journal of medical informatics, 1998)
The specialized university curriculum for medical informatics (MI) at the University of Heidelberg/School of Technology Heilbronn is one of the oldest educational approaches in the field of MI and has been successful now for 25 years with about 1000 graduates (Diplom-Informatikerin der Medizin or Diplom-Informatiker der Medizin). It belongs to the category of dedicated master's programs for MI and is based on the concept of MI as a medical discipline of its own. It is oriented towards the total spectrum of MI ranging from health care economics, biosignal and medical image processing, medical documentation, to information and knowledge processing in medicine. It is a 4.5 years program with a strong emphasis on the methodological foundations of MI and on practical education in a number of specific laboratories. A total of 35 students are admitted each semester and in total about 440 students are enrolled. The faculty consists of 17 full-time members and about 25 part-time lecturers. The authors report on characteristics, structure and contents of the new fifth version of the curriculum and discuss the features of a specialized curriculum for MI with respect to the challenges for MI in the 21st century.